PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Dewi, Rita; Wahyuningrum, Endang; Aisyah, Siti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the improvement of fifth-grade students’ mathematical critical thinking skills and mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model at SD Peradaban Serang. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The population consisted of all fifth-grade students in the 2024/2025 academic year, with two classes selected as the experimental and control groups, each comprising 21 students. The research instruments included an essay-based mathematical critical thinking test developed according to Facione’s indicators (interpretation, analysis, evaluation, and inference) and a multiple-choice mathematics achievement test, all of which met validity and reliability requirements. Data were analyzed using an independent samples t-test and N-Gain analysis. The results indicated that the implementation of PBL had a significant effect on mathematical critical thinking skills (t = −3.317; p = 0.002) and mathematics learning outcomes (t = −2.241; p = 0.031). Mathematically, the mean N-Gain score for mathematical critical thinking in the experimental class was 0.5236 (52.36%), which was higher than that of the control class at 0.4966 (49.66%), with a difference of 2.70%; both were categorized as moderate. Meanwhile, the mean N-Gain score for mathematics learning outcomes in the experimental class was 0.3715 (37.15%), classified as moderate, and higher than that of the control class at 0.2352 (23.52%), which was categorized as low. These findings indicate that the Problem Based Learning model is more effective in improving students’ mathematical critical thinking skills and mathematics learning outcomes at the elementary school level. ABSTRAK Penelitian ini bertujuan untuk menganalisis peningkatan kemampuan berpikir kritis matematis dan hasil belajar matematika siswa kelas V SD Peradaban Serang melalui penerapan model Problem Based Learning (PBL). Penelitian menggunakan pendekatan kuantitatif dengan metode kuasi eksperimen dan desain pretest–posttest control group. Populasi penelitian meliputi seluruh siswa kelas V tahun ajaran 2024/2025, dengan dua kelas yang dipilih sebagai kelas eksperimen dan kelas kontrol, masing-masing berjumlah 21 siswa. Instrumen penelitian terdiri atas tes uraian kemampuan berpikir kritis matematis berdasarkan indikator Facione (interpretasi, analisis, evaluasi, dan inferensi) serta tes hasil belajar matematika berbentuk pilihan ganda, yang telah memenuhi kriteria validitas dan reliabilitas. Analisis data dilakukan menggunakan independent samples t-test dan perhitungan N-Gain. Hasil penelitian menunjukkan bahwa penerapan PBL berpengaruh signifikan terhadap kemampuan berpikir kritis matematis (t = −3,317; p = 0,002) dan hasil belajar matematika (t = −2,241; p = 0,031). Secara matematis, nilai rata-rata N-Gain kemampuan berpikir kritis matematis pada kelas eksperimen sebesar 0,5236 (52,36%) lebih tinggi dibandingkan kelas kontrol sebesar 0,4966 (49,66%), dengan selisih peningkatan sebesar 2,70% dan keduanya berada pada kategori sedang. Sementara itu, nilai N-Gain hasil belajar matematika pada kelas eksperimen sebesar 0,3715 (37,15%) termasuk kategori sedang dan lebih tinggi dibandingkan kelas kontrol sebesar 0,2352 (23,52%) yang berada pada kategori rendah. Temuan ini menunjukkan bahwa model Problem Based Learning lebih efektif dalam meningkatkan kemampuan berpikir kritis matematis dan hasil belajar matematika siswa sekolah dasar.